The coins of Herod : a modern analysis and die classification - Ariel, Donald T. (Ancient Judaism and Early Christianity, 2012)
Herod, ruler of Judea at a pivotal time (40-4 BCE) in the region's history, was Rome's most famous client king. In this volume, Herod's coinage benefits from a comprehensive reappraisal. The coins and dies have been thoroughly examined, resulting in innovative iconographic and technological interpretations. Study of the coins' presence in hoards, their archaeological contexts and geographical distribution, together with other typological, epigraphic and numismatic observations, have aided in establishing that all of the types were minted in Jerusalem. A new relative chronology of Herod's dated and undated coins is the most important by-product of this study. Finally, an attempt is made to peg this seriation to known events within the king's reign.